Reflections on the Environment and the Way of Life of Brazilian Artisanal Fishermen (Global Journal of Human-Social Science, 2024)
Extractive Reserves are territorial spaces in Brazil created by Law No 9 985 2000 with the objective of protecting the livelihoods and culture of traditional Brazilian extractivist populations as well as ensuring the sustainable use of natural resources in these areas The recipients of this protection are artisanal fishermen who inhabit the Brazilian coast and depend on fishing resources to survive It so happens that this protection is questioned given the problems that threaten these populations such as disorderly fishing pollution tourism in addition to the absence of public policies for them In order to analyze the Jequi Lagoon Marine Extractive Reserve as a form of protection for artisanal fishermen a descriptive and exploratory study was developed of a qualitative nature with the artisanal fishermen of this conservation unit
Keywords: jequiá lagoon marine; extractive reserve; artisanal fishermen; law protection; public policies